WHO IS INDIGENOUS? DEFINITIONS OF INDIGENEITY - Erika Sarivaara; Kaarina Maatta; Satu Uusiautti (European Scientific Journal, ESJ, 2014)
This article is based on indigenous research focusing on indigeneity and membership in indigenous group at the individual level. The position and rights of indigenous peoples gained a foothold at the political arenas of the world and in international agreements since the turn of the 1990s when indigenous peoples and minorities were started to be distinguished from each other. Indigenous peoples were considered to have collective rights regarding control over certain areas colonized by the mainstream population at a certain point of history. The aim is first to review the different membership criteria within different Indigenous groups in the world, and then to emphasize the definition of Sámi in Finland and its individual-level challenges. As a result of this paper, it seems that the individual-level indigenous identity does not necessarily correspond with the membership in indigenous group. When indigenous identity is not being accepted for one reason or another it violates the international declarations for indigenous peoples and may cause challenges both at individual and societal levels within indigenous communities.